Learning health 'safety' within non-technical skills interprofessional simulation education: a qualitative study. Issue 1 (1st January 2017) - Gordon, Morris; Fell, Christopher W. R.; Box, Helen; Farrell, Michael; Stewart, Alison
ABSTRACT: Background : Healthcare increasingly recognises and focusses on the phenomena of 'safe practice' and 'patient safety.' Success with non-technical skills (NTS) training in other industries has led to widespread transposition to healthcare education, with communication and teamwork skills central to NTS frameworks. Objective: This study set out to identify how the context of interprofessional simulation learning influences NTS acquisition and development of 'safety' amongst learners. Methods : Participants receiving a non-technical skills (NTS) safety focussed training package were invited to take part in a focus group interview which set out to explore communication, teamwork, and the phenomenon of safety in the context of the learning experiences they had within the training programme. The analysis was aligned with a constructivist paradigm and took an interactive methodological approach. The analysis proceeded through three stages, consisting of open, axial, and selective coding, with constant comparisons taking place throughout each phase. Each stage provided categories that could be used to explore the themes of the data. Additionally, to ensure thematic saturation, transcripts of observed simulated learning encounters were then analysed. Results : Six themes were established at the axial coding level, i.e., analytical skills, personal behaviours, communication, teamwork, context, and pedagogy. Underlying these themes, two principal concepts emerged, namely: intergroup contact anxiety – as both a result of and determinant of communication – and teamwork, both of which must be considered in relation to context. These concepts have subsequently been used to propose a framework for NTS learning. Conclusions : This study highlights the role of intergroup contact anxiety and teamwork as factors in NTS behaviour and its dissipation through interprofessional simulation learning. Therefore, this should be a key consideration in NTS education. Future research is needed to consider the role of the affective non-technical attributes of intergroup contact anxiety and teamwork as focuses for education and determinants of safe behaviour. Abbreviations: AUM: Anxiety/uncertainty management; NTS: Non-technical skills; TINSELS: Training in non-technical skills to enhance levels of medicines safety